The first ladies [large type] - Benedict, Marie; Murray, Victoria Christopher (Random House large print., 2023)
Initially drawn together because of their shared belief in women's rights and the power of education, civil rights activist Mary McLeod Bethune and First Lady Eleanor Roosevelt fight together for justice and equality, holding each other's hands through tragedy and triumph.